Do tree species affect decadal changes in soil organic carbon and total nitrogen stocks in Danish common garden experiments?. (23rd December 2021) - Steffens, Christina; Beer, Christian; Schelfhout, Stephanie; De Schrijver, An; Pfeiffer, Eva‐Maria; Vesterdal, Lars
Abstract: Temperate forest soils are often considered as an important sink for atmospheric carbon (C), thereby buffering anthropogenic CO2 emissions. However, the effect of tree species composition on the magnitude of this sink is unclear. We resampled a tree species common garden experiment (six sites) a decade after initial sampling to evaluate whether forest floor (FF) and topsoil organic carbon (Corg ) and total nitrogen (Nt ) stocks changed in dependence of tree species (Norway spruce— Picea abies L., European beech— Fagus sylvatica L., pedunculate oak— Quercus robur L., sycamore maple— Acer pseudoplatanus L., European ash— Fraxinus excelsior L. and small‐leaved lime— Tilia cordata L.). Two groups of species were identified in terms of Corg and Nt distribution: (1) Spruce with high Corg and Nt stocks in the FF developed as a mor humus layer which tended to have smaller Corg and Nt stocks and a wider Corg :Nt ratio in the mineral topsoil, and (2) the broadleaved species, of which ash and maple distinguished most clearly from spruce by very low Corg and Nt stocks in the FF developed as mull humus layer, had greater Corg and Nt stocks, and narrow Corg :Nt ratios in the mineral topsoil. Over 11 years, FF Corg and Nt stocks increased most under spruce, while small decreases in bulk mineral soil (esp. in 0–15 cm and 0–30 cm depth) Corg and Nt stocks dominated irrespective of species. Observed decadal changes were associated with site‐related and tree species‐mediated soil properties in a way that hinted towards short‐term accumulation and mineralisation dynamics of easily available organic substances. We found no indication for Corg stabilisation. However, results indicated increasing Nt stabilisation with increasing biomass of burrowing earthworms, which were highest under ash, lime and maple and lowest under spruce. Highlights: We studied if tree species differences in topsoil Corg and Nt stocks substantiate after a decade. The study is unique in its repeated soil sampling in a multisite common garden experiment. Forest floors increased under spruce, but topsoil stocks decreased irrespective of species. Changes were of short‐term nature. Nitrogen was most stable under arbuscular mycorrhizal species.